Mechanism of fungal remediation of wetland water: Stropharia rugosoannulata as promising fungal species for the development of biofilters to remove clinically important pathogenic and antibiotic resistant bacteria in contaminated water - Sen, Keya; Llewellyn, Marina; Taheri, Babak; Turner, Robert J.; Berglund, Tanner; Maloney, Kellen (Frontiers in Microbiology, 2023)
Mycoremediation uses mushroom forming fungi for remediation of sites contaminated with biotic and abiotic contaminants. The root-like hyphae of many fungi, the mycelia, have been used to remediate soil and water. In this study mushroom mycelia biofilters were evaluated for remediation efficacy of wetland water polluted with crow feces containing antibiotic resistant (AMR) bacteria. Three strains of fungi, Pleurotus ostreatus, Stropharia rugosoannulata, and Pleurotus pulmonarius, were allowed to develop dense mycelia for 3-5 weeks on wood chips within cylindrical jars. Biofilter jars were incubated with wetland water (WW) obtained from a crow roost area that was additionally spiked with AMR bacteria isolated from previous crow fecal collections. E. coli, Staphylococcus aureus, Enterococcus faecium, Campylobacter jejuni, Klebsiella pneumoniae, Pseudomonas aeruginosa, and Salmonella enteritidis were added at concentrations of 1,500–3,500 CFU/100 ml. Remediation was calculated from bacterial counts or gene copy numbers (GCN), before and after passage of water through jars. Stropharia and P. pulmonarius biofilters remediated all bacteria, but Klebsiella, in the range of 43-78%, after 1 h. Incubation of water for 24 h showed Stropharia remediation to be superior relative to other tested fungi. Percent remediation varied as follows: S. aureus-100%, E. faecium-97%, C. jejuni-59%, P. aeruginosa-54%, E. coli-65% and S. enteritidis-27%. The mechanism of remediation was tested by removing the mycelium from the biofilter column after passage of water, followed by extraction of DNA. Association of bacterial DNA with the mycelia was demonstrated by qPCR for all bacteria, except S. aureus and Salmonella. Depending on the bacteria, the GCN ranged from 3,500 to 54,000/250 mg of mycelia. Thus, some of the ways in which mycelia biofilters decrease bacteria from water are through bio-filtration and bio-absorption. Active fungal growth and close contact with bacteria appear necessary for removal. Overall these results suggest that mushroom mycelia biofilters have the potential to effectively remediate water contaminated with pathogenic and AMR bacteria.